2015
DOI: 10.3389/fimmu.2014.00673
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy by Targeting IDO1/TDO and Their Downstream Effectors

Abstract: The tryptophan (TRP) to kynurenine (KYN) metabolic pathway is now firmly established as a key regulator of innate and adaptive immunity. A plethora of preclinical models suggests that this immune tolerance pathway – driven by the key and rate-limiting enzymes indoleamine-2,3-dioxygenase and TRP-2,3-dioxygenase – is active in cancer immunity, autoimmunity, infection, transplant rejection, and allergy. Drugs targeting this pathway, specifically indoleamine-2,3-dioxygenase, are already in clinical trials with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
291
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(294 citation statements)
references
References 55 publications
(69 reference statements)
3
291
0
Order By: Relevance
“…Evidence suggests that the immune response may be impaired by upregulation of multiple checkpoint inhibitors and that these inhibitory pathways are upregulated in microsatellite unstable colorectal carcinomas. 18,[27][28][29] Most of these studies, however, classify microsatellite unstable colorectal carcinomas as a single group and do not consider the histologic heterogeneity of microsatellite unstable colorectal carcinomas. As such, we hypothesized Figure 1 Percentage of cases by histologic subtype demonstrating epithelial and stromal staining for IDO-1, tRNA(trp) or WARS, GBP5, and PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the immune response may be impaired by upregulation of multiple checkpoint inhibitors and that these inhibitory pathways are upregulated in microsatellite unstable colorectal carcinomas. 18,[27][28][29] Most of these studies, however, classify microsatellite unstable colorectal carcinomas as a single group and do not consider the histologic heterogeneity of microsatellite unstable colorectal carcinomas. As such, we hypothesized Figure 1 Percentage of cases by histologic subtype demonstrating epithelial and stromal staining for IDO-1, tRNA(trp) or WARS, GBP5, and PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…It provides an ideal immune-sanctuary site for tumor growth by its ability to locally mediate T-cell inactivation, tolerance and apoptosis [39]. For instance, the liver is rich in tryptophan 2,3-dioxygenase that degrades tryptophan along the kynurenine pathway, which might explain a local T-cell suppressive immune microenvironment [40]. Indeed, clinical studies in cutaneous melanoma have shown relatively poor responses to anti-PD-1 therapy in the setting of liver metastasis, with the liver metastasis also demonstrating lower rates of PD-L1 expression [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Local depletion of TRP suppresses T cell proliferation and induces cell death [43] . AHR activation reportedly induces differentiation of Treg cells [44] . …”
Section: T Cellsmentioning
confidence: 99%